Long-term effect of acidic pH on the surface microhardness of ProRoot mineral trioxide aggregate, Biodentine, and total fill root repair material putty - (:unkn) unknown (Wolters Kluwer Medknow Publications, 2021)
Background: The purpose of this study was to compare the microhardness values of ProRoot mineral trioxide aggregate (MTA), Biodentine, and total fill root repair material (TF-RRM) Putty at varying pH and times. Materials and Methods: In this laboratory experiment, materials were mixed and placed in cylinder blocks with internal dimensions of 6 mm × 4 mm. Ten samples of each material were soaked in buffered solutions of butyric acid with 4.4, 5.4, 6.4, and 7.4 pH values and stored at 37°C in 100% humidity. The samples were submitted to the microhardness test at the end of 1 week and then 1 month. Multivariate analysis of variance and Tukey honestly significant difference tests were carried out to compare the mean values at a significance level of P < 0.05. Results: Low pH caused a significant decrease in the microhardness values of all samples. Surface microhardness increased with time (P < 0.0001). The microhardness values of Biodentine were significantly greater than those of ProRoot MTA and TF-RRM putty (P < 0.0001). The lowest microhardness values were recorded for TF-RRM putty groups regardless of the pH of the environment and the evaluation time. Conclusion: An acidic environment impaired the surface microhardness of all root repair materials tested. Overall, the mean surface microhardness of TF-RRM Putty was lower than those of ProRoot MTA and Biodentine. Biodentine showed the greatest microhardness values at all pH values, regardless of the evaluation time. © 2021 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Hardness tests; inflammation; mineral trioxide aggregate; root canal filling materials; tricalcium silicate